2017
DOI: 10.1016/j.physbeh.2017.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ambient odors on food intake, saliva production and appetite ratings

Abstract: The aim of this study was to investigate the effect of ambient odor exposure on appetite, salivation and food intake. 32 normal-weight young women (age: 21.4±5.3year; BMI: 21.7±1.9kg/m) attended five test sessions in a non-satiated state. Each participant was exposed to ambient odors (chocolate, beef, melon and cucumber), in a detectable but mild concentration, and to a control condition (no-odor exposure). During each condition, at different time points, participants rated appetite for 15 food products, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 54 publications
7
62
0
Order By: Relevance
“…For this purpose, a combination of SDS-PAGE, which allowed protein separation in the total of participants, was combined with 2-DE for a deeper separation of the proteins, in a sub-sample. Recently, it was shown that salivary flow rate increases in response to food odours [9,10] and that increase was also observed in the present study, where smelling bread resulted in rise in the volume of saliva produced. This increase in salivation induced by food smelling is part of the cephalic phase response, with the function of preparing the body to optimize nutrient processing throughout the gastrointestinal tract [23].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For this purpose, a combination of SDS-PAGE, which allowed protein separation in the total of participants, was combined with 2-DE for a deeper separation of the proteins, in a sub-sample. Recently, it was shown that salivary flow rate increases in response to food odours [9,10] and that increase was also observed in the present study, where smelling bread resulted in rise in the volume of saliva produced. This increase in salivation induced by food smelling is part of the cephalic phase response, with the function of preparing the body to optimize nutrient processing throughout the gastrointestinal tract [23].…”
Section: Discussionsupporting
confidence: 88%
“…There is empirical and scientific evidence that the odour of a palatable food induces saliva secretion. Exposure to odours of chocolate or beef were observed to increase salivation compared to a situation of absence of odours [9] and a recent study demonstrated that this rise in salivary flow rate after food-odour stimulation does not occur in response to non-food odour [10].…”
Section: Introductionmentioning
confidence: 99%
“…The odor-enhanced appetite for congruent food items was also found in other studies [23], although the effect has not been consistently observed [25]. Exposure to congruent ambient scents was also found to increase consumers' satiety, i.e., their feeling of fullness ([26], also see [27]), and modulate food intake [24,25]. In addition, when both orthonasal and retronasal pathways were activated by matching scents, the amount of food items consumed was found to diminish [17,21,28].…”
Section: Introductionsupporting
confidence: 55%
“…For example, Ramaekers et al [21] demonstrated that food odors (e.g., bread or chocolate) increased consumers' appetite and directed their choices toward congruent food items. The odor-enhanced appetite for congruent food items was also found in other studies [23], although the effect has not been consistently observed [25]. Exposure to congruent ambient scents was also found to increase consumers' satiety, i.e., their feeling of fullness ([26], also see [27]), and modulate food intake [24,25].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation